Modelling collective Yawuru values along the foreshore of Roebuck Bay, Western Australia using fuzzy logic. (December 2016) - Potter, Sandra; Doran, Bruce; Mathews, Dean
Abstract: The cadastral model has played a key role in Indigenous dispossession in settler states. Yet, the recognition of Indigenous land rights, which has increased globally since the 1960s, frequently requires Indigenous communities to directly engage with this spatial model. In Australia, native title claimants must use entity-based models of space to delineate their traditional territories during the claim process. They must also engage with planning and development documents which use the cadastral model of space to assert and defend their rights following native title recognition. This is often problematic as Indigenous spatial ontologies emphasise complexity and continuity which is inimical to the 'crisp' representations of cadastral space. This study explores the potential of a fuzzy index modelling approach to represent cultural values using a case study from Broome, Western Australia. Sketch mapping, fuzzy index modelling and combinatory techniques were used to produce a model of several cultural values held by the Yawuru community for the in-town foreshore of Roebuck Bay. This model was overlaid on local planning documents to provide the Yawuru community with strategic intelligence for post native title governance. The experience of co-producing this model suggests that such techniques may assist Indigenous communities to engage with settler structures. This implies that policies which fail to extend analytical capacity to interested native title groups as part of programmes of spatial enablement continue to perpetuate historical processes of colonial domination. Highlights: The use of fuzzy index modelling to represent Indigenous cultural values was tested. A model of several cultural values held by the Yawuru community for Broome's in-town foreshore was produced. Strategic intelligence was produced by overlaying this model on local planning documents. Fuzzy modelling techniques may assist Indigenous peoples in engaging with settler structures.